Post-Operative Radiotherapy in Prostate Cancer: Is It Time for a Belt and Braces Approach? - Giraud, Nicolas; Benziane-Ouaritini, Nicolas; Schick, Ulrike; Beauval, Jean-Baptiste; Chaddad, Ahmad; Niazi, Tamim; Faye, Mame Daro; Supiot, Stéphane; Sargos, Paul; Latorzeff, Igor (Frontiers in Oncology, 2021)
Around 30% of patients treated with radical prostatectomy (RP) for prostate cancers experience biochemical recurrence (BCR). Post-operative radiation therapy (RT) can either be offered immediately after the surgery in case of aggressive pathological features or proposed early if BCR occur. Until recently, little data were available regarding the optimal RT timing, protocol, volumes to treat and the benefit of adding androgen deprivation therapies to post-operative RT. In this review, we aim to pragmatically discuss current literature data on these points. Early salvage RT appears to be the optimal post-operative approach, improving oncological outcomes especially with low prostate-specific antigen (PSA) levels, as well as sparing several unnecessary adjuvant treatments. The standard RT dose is still 64-66 Gy to the prostate bed in conventional fractionation, but hypofractionation protocols are emerging pending on late toxicity data. Several scientific societies have published contouring atlases, even though heterogeneous and deserving future consensus. During salvage RT, the inclusion of pelvic lymph nodes is also controversial, but preliminary data show a possible benefit for PSA > 0.34ng/mL at the cost of increased hematological side-effects. Concomitant ADT and its duration are also discussed, possibly advantageous (at least in terms of metastasis-free survival) for PSA rates over 0.6 ng/mL, taking into account life expectancy and cardio-vascular comorbidities. Intensified regimens, for instance with new generation hormone therapies, could further improve outcomes in carefully selected patients. Finally, recent advances in molecular imaging, as well as upcoming breakthroughs in genomics and artificial intelligence tools could soon reshuffle the cards of the current therapeutic strategy.